Analysis And Formulation of Marketing Strategies in Third Party Logistics (3pl) to Increase Sales - Sitompul, Rodrick M. K. (Master of Management, Faculty of Economics and Business, Diponegoro University, 2024)
The logistics business is one of the business sectors that has a high growth rate, this is in line with the increasing needs of people's lives accompanied by increasingly sophisticated technological developments. ABC Company is the grandson of the Pertamina group and is a subsidiary of Pertamina Patra Niaga as a Commercial and Trading sub-holding. Currently, the marketing strategy carried out by ABC is still not good. There is no specific marketing strategy that can directly attract customers outside of the parent company. This study aims to formulate and analyze marketing strategies using external and internal analysis.